Characteristics and outcomes of hemodialysis patients with COVID-19: a retrospective single center study - Luo, Yongwen (PeerJ, 2020)
BACKGROUND: The coronavirus 19 (COVID-19) pandemic has heightened the threat to the health and lives of patients with comorbid diseases. Infection by COVID-19 is especially detrimental to patients on hemodialysis. In this study, we evaluated the clinical characteristics, laboratory findings, treatments and prognoses of hemodialysis patients with COVID-19. METHODS: A total of 16 hemodialysis patients with COVID-19 were recruited from Wuhan Fourth Hospital from 5 February to 20 March 2020 for a retrospective, single-center study. A total of 62 non-dialysis patients with COVID-19 were the control group. We collected data on the clinical characteristics, laboratory findings, treatments, and clinical outcomes of patients affected by the virus. RESULTS: Hemodialysis patients with COVID-19 had a lower incidence of fever (P = 0.001) and relatively higher incidence of pre-admission comorbidities and shortness of breath than non-dialysis patients with COVID-19 (75% vs. 61%, P = 0.467 50% vs. 33.87%, P = 0.248 ). Hemodialysis patients had lower levels of hemoglobin (P < 0.001), white blood cell counts (P = 0.015), neutrophils (P = 0.016), AST (P = 0.037), ALT (P < 0.001) and procalcitonin (P < 0.001), and higher levels of D-dimer (P < 0.001) and thrombin time (P < 0.001). Hemodialysis patients had a higher incidence of pulmonary effusion, cord-like high-density shadows, pleural thickening, and atelectasis (P < 0.05). Hemodialysis patients also had relatively higher rates of mortality and prolonged hospital stays compared with the control group. CONCLUSIONS: Hemodialysis patients typically present with multiple comorbidities and are considered to be a high-risk group for COVID-19 infections. Hemodialysis patients with COVID-19 may have prolonged hospital stays and unfavorable prognoses and should be closely monitored.